¿Uno de los nuestros?: otra vuelta de tuerca al marxismo de Karl Polanyi - Rodríguez, Sergio Braulio Véliz (El Buho: Revista electrónica de la Asociación Andaluza de Filosofía, 2022)
Este ensayo trata de situar la obra de Karl Polanyi en la tradición del pensamiento marxista heterodoxo, respondiendo a las objeciones que se han planteado en contra de tal filiación. Se analizan para ello los conceptos fundamentales del pensamiento del autor desde un punto de vista marxista: la “economía sustantiva” y la “economía formal”, la “falacia economicista”, la “incrustación” (Embeddedness) de la economía, las “mercancías ficticias” y el “doble movimiento”.
Keywords: Marxism; double movement; economi; economistic fallacy; embeddedness; embeddness; fictitious commodities; formal economy; substantive economy

Discussions around Argentine Capitalism: Economic Debate and Contribution of Karl Polanyi for Our Days - Rossi, Ignacio Andrés (2022)
The article proposes to address the current discussions about national capitalism and the Argentine economy from a set of canonical ideas of the work of Karl Polanyi. Argentina, which for several decades has been going through recurring crises in its economic model, awakens a plurality of voices from social scientists and specialized journalists who debate the problems, limitations and projections of national capitalism. For this, we have surveyed these discussions, to a greater extent, from the specialized press and the recently published bibliography, paying attention to the theoretical, interpretative and ideological proposals that allow us to generate relationships with Polanyi's theory. It was concluded that the latter's ideas about the functioning of capitalism, markets, the State and contemporary social dynamics provide significant conceptual background to frame the current discussions among social scientists about the Argentine economy.
Keywords: Argentina; capitalism; development; stability; state